Boosting Digital Literacy: Empowering Mathematics Students of Bachelor Degree for Learning C Programming - K.C., Subash (Dhaulagiri Journal of Contemporary Issues, 2023)
This study explores the impact of a general digital literacy module on students pursuing a bachelor’s degree in Mathematics under Humanities and Social Sciences at Tribhuvan University. The module was targeted to develop fundamental skills for learning C Programming. Employing a participatory action research approach, a module was developed based on the students’ prior knowledge and their ICT course. A ten-day instructional intervention was conducted, utilizing cooperative techniques. The module aimed to establish a foundation for learning the ICT component within the mathematics program. To assess the module’s effectiveness, classroom observations and students interviews were employed. The results indicate that the module successfully connects the ICT component with the mathematics program, equipping students with essential digital literacy skills crucial for comprehending the course content. Additionally, the findings emphasize the significance of providing a bridging module to support students’ prior knowledge and adequately prepare them for the program’s curriculum. This study contributes to enhance digital literacy skills in mathematics education for students in humanities and social sciences, facilitating their academic growth and future success.